Constructing scientific explanations through premise–reasoning–outcome (PRO): an exploratory study to scaffold students in structuring written explanations - Tang, Kok-Sing (Routledge, 2016)
This paper reports on the design and enactment of an instructional strategy aimed to support students in constructing scientific explanations. Informed by the philosophy of science and linguistic studies of science, a new instructional framework called premise–reasoning–outcome (PRO) was conceptualized, developed, and tested over two years in four upper secondary (9th–10th grade) physics and chemistry classrooms. This strategy was conceptualized based on the understanding of the structure of a scientific explanation, which comprises three primary components: (a) premise – accepted knowledge that provides the basis of the explanation, (b) reasoning – logical sequences that follow from the premise, and (c) outcome – the phenomenon to be explained. A study was carried out to examine how the PRO strategy influenced students’ written explanations using multiple data sources (e.g. students’ writing, lesson observations, focus group discussions). Analysis of students’ writing indicates that explanations with a PRO structure were graded better by the teachers. In addition, students reported that the PRO strategy provided a useful organizational structure for writing scientific explanations, although they had some difficulties in identifying and using the structure. With the PRO as a new instructional tool, comparison with other explanation frameworks as well as implications for educational research and practice are discussed.